2017
DOI: 10.18483/ijsci.1212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Overload on Growth and Intestinal Mucosa in Rats

Abstract: Objective: To detect the mechanism of excess iron intake on growth and intestinal mucosa in rats. Methods: Forty-eight male Wistar rats were randomly divided into four groups: Low Iron Group, Normal Iron Group, Medium Iron Group and High Iron Group upon daily iron intake of 7mg/kg, 16.8mg/kg, 35mg/kg, 70mg/kg respectively via fodder for eight weeks. The general condition, body weight and food intake were documented simultaneously. Serum level of Ferritin, IL-6 and IL-10 were detected using ELISA. The observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
2
0
0
Order By: Relevance
“…Some of intestinal villi were eroded and others were atrophied, the columnar epithelium showed hyperplasia, and also numerous goblet cells, Iron laden cells, and demarcated intraepithelial lymphocytes were observed in the lamina propria in duodenum sections and absent most of villi in the ileum. These results were in agreement with [28] who reported that high iron dose in rats caused irregular villous morphology and necrotic intestinal mucosal epithelium, suggesting that excessive iron caused intestinal inflammatory injury in rats. The pathological alterations of small intestine induced by iron were attributed to affection of intestinal hemostasis either by altering intestinal microbial formation, or by oxidative stress, or by inflammation [56, 57].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some of intestinal villi were eroded and others were atrophied, the columnar epithelium showed hyperplasia, and also numerous goblet cells, Iron laden cells, and demarcated intraepithelial lymphocytes were observed in the lamina propria in duodenum sections and absent most of villi in the ileum. These results were in agreement with [28] who reported that high iron dose in rats caused irregular villous morphology and necrotic intestinal mucosal epithelium, suggesting that excessive iron caused intestinal inflammatory injury in rats. The pathological alterations of small intestine induced by iron were attributed to affection of intestinal hemostasis either by altering intestinal microbial formation, or by oxidative stress, or by inflammation [56, 57].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, there were increased IL6 and reduction of IL10 in small intestinal mucosal tissues of iron overloaded rats indicating increased intestinal mucosal inflammatory response; these findings are consistent with Yi-chen et al [28] who reported increased levels of IL-6 and reduction of IL10 in intestinal tissue of high-ferrous sulfate administrated rats; another study found increased duodenal mucosal cytokines expression on administration of high iron diet in porcine models [51]. The intestinal inflammatory response associated with iron overload may be attributed to oxidative stress induced by excess cellular iron that increased intestinal mucosal permeability leading to antigen and pathogen translocation though epithelial cells [52].…”
Section: Discussionsupporting
confidence: 93%